Performance Evaluation of Sharia Economics Study Program, Faculty of Economics and Islamic Business, State Islamic Institute of Purwokerto - Jamal Abdul Aziz; Sulasih Sulasih (Budapest International Research and Critics University, 2022)
Performance evaluation is needed by each Study Program to understand the achievement of advantages and at the same time the weaknesses and shortcomings of targets that have not been achieved. In addition, the evaluation of the study program's performance is also one of the requirements for applying for accreditation. This research focuses on evaluating the performance of the Islamic Economics Study Program IAIN Purwokerto in 2018-2019 by basing it on the Study Program accreditation instrument from BAN-PT. This research only reveals quantitative data as requested in the LKPS instrument. Data analysis was carried out using an assessment instrument from BAN-PT in the form data category, which was about half of the overall assessment items on the instrument. Based on real data in the field, the average score is 3 (very good). With quantitative data like this, even harder efforts are needed to be able to increase the score in order to achieve excellence.